Growth and Biomass Production Potential of Acacia jacquemontii Benth. in Different Soil Conditions in Hot Arid Region of India - Mertia, R S; Prasad, Rajendra; Kandpal, B K (Annals of Arid Zone, 2016)
The growth and biomass production potential of Acacia jacquemontii, an endangered shrub of Indian arid zone, was studied under deep, medium and shallow soils. Maximum plant growth and above-ground biomass was obtained in deep soil, where as it was least in shallow soil. Polynomial linear relationship existed between the age and plant height, stem diameter and number of stems/thicket. Soil conditions had no significant bearings on proportionate allocation of different components of total accumulated biomass. Accumulation of stem wood and branches/twigs biomass was the maximum in deep soil followed by medium and shallow soils. However, foliage yield was at par in medium and shallow soils. Its profuse growth habit and multi-stem character make it suitable species for sand dune stabilization, as flank rows in shelterbelt plantations and for social forestry programs. Key words: Multipurpose shrub, Thar Desert, above-ground biomass, Acacia jacquemontii, threatened species, soil depth.